Language, Logic, and Computation : 12th International Tbilisi Symposium, TbiLLC 2017, Lagodekhi, Georgia, September 18-22, 2017, Revised Selected Papers /: 12th International Tbilisi Symposium, TbiLLC 2017, Lagodekhi, Georgia, September 18-22, 2017, Revised Selected Papers. (2019) - Unknown
No abstract available